The role of extra-curricular activities in consolidating the values of citizenship and ways of promoting it in post-primary government education in the Sultanate of Oman from the viewpoint of its specialists - Al-Saiari, Nasser Abdullah Mahroos (Journal of Educational and Psychological Sciences, 2023)
The study aims to identify the role of extracurricular activities in consolidating the values of citizenship and ways to promote it in post-primary public education in the Sultanate of Oman from the point of view of its specialists (Dhofar Governorate as a model), using the descriptive analytical approach, and a questionnaire and a sample of (65) male and female non-curricular activities specialists, from the total study population of (67). It included two sections: the first included the demographic data of the sample, and the second (48) phrases that dealt with activities and procedures that show the levels of the role of extra-curricular activities and ways of promoting it in consolidating the values of citizenship among students in the four fields of study. Water comes first, followed by the values of community participation, then the values of national duties, and finally the values of national rights. B- The ways to promote the role of extra-curricular activities in consolidating the values of citizenship in the fields of study among students came with a high relative importance based on its general arithmetic mean of (4.19). C- There are no statistically significant differences between the opinions of the sample about the levels of the role of extra-curricular activities in consolidating the values of citizenship in the fields of study among students according to the two variables (gender- practical experience). Accordingly, the study recommended emphasizing the necessity of transforming the programs and events mentioned in the study into a reality in the schools of the Sultanate in general, and the schools of Dhofar Governorate in particular. With attention being directed to more studies and research in the field of study due to its scarcity at the level of the Sultanate.
Keywords: role; extracurricular activities; rooting; citizenship values; promotion